THE ROLE OF THE NURSES IN HEALTH PROMOTION FROM THE VIEW POINT OF PATIENTS AT KINGABDULLAH HOSPITAL IN IRBID - Falastine R. Hamdan; Mariam Kawafhah (European Scientific Journal, ESJ, 2015)
This study aimed to know the viewpoint of patients at King Abdullah Hospital on the role of nurses in health promotion in general, and also aimed to investigate the effect of gender, age, area of residence, and academic level on the point of view of patients. The study sample consisted of 120 patients 63 males and 57 females at King Abdullah Hospital. Means and standard deviations and t-test were used to analyze the results. The results showed that there were statistically significant differences in the views of the patients on the role of nurses in health promotion in general, also showed a statistically significant differences at the level of significance (α ≥ 0,05) in their views attributed to the age, as there are statistically significant differences at the level of significance (α ≥ 0,05) in their views attributed to gender, and results also showed the existence of clear statistically significant differences in the views of the patients on the role of nurses in health promotion due to the Academic level and area of residence variables.